Bottomed mesons and baryons production in pp collisions at s=5 TeV LHC energy within a Coalescence plus Fragmentation approach - Vincenzo Minissale; Vincenzo Greco; Salvatore Plumari (Physics Letters B)
Recent experimental data from pp collisions have shown a significant increase in heavy baryon production leading to a baryon over meson ratio which is one order of magnitude higher than in elementary collisions (e+e−, ep). From a theoretical point of view this large production of baryon can be explained with hadronization via quark coalescence assuming a QGP medium in pp collisions. In this study, we extend this analysis to include hadrons containing bottom quarks. Employing a coalescence plus fragmentation approach, we present predictions for pT spectra and the heavy baryon/meson ratio of bottomed hadrons with and without strangeness content, specifically: B0¯, Bs, Λb, Ξb0,−, Ωb, and the Bc meson. We have found that coalescence is the dominant mechanism in the B meson production, especially at low momenta, at variance with what found in the charm sector where the D mesons were mainly produced via fragmentation. Our model predicts a Λb/B0¯≈0.6−0.9 and a Ξb0/B0¯ ratio around 0.2−0.3 at very low transverse momentum, ratios which are about 1.5 larger than those of the corresponding charmed hadron ratios at the same collision energy. Furthermore, we discuss the relative ratios between charmed and bottomed hadrons, emphasizing how they can provide information about the distribution of charm and bottom quarks and, if experimentally observed, how they would further support the idea of quark-gluon plasma formation even in small collision systems.